Nulidade no auto de infração - Criales, Marly Moreira Couto (2015)
This paper s purpose is to study the invalidities on the tax notice for disrespect of mandatory requirements for its transcription with the purpose of determining the criteria for the classification of types of invalidities, defects and their effects, related to the requirements of act 10 of decree 70.235 /72. The study begins with the understanding of the rules of law as a construction of the human being to interpret the texts of law and give them meaning. It works invalidity as the antithesis of validity, and analyzes the concepts of validity, existence and effectiveness of legal standards. Then, it studies the tax notice as an administrative act to define that their requirements for transcription are composed of intrinsic elements and assumptions of validity. Finally, it analyzes the theories of invalidity and its application in Tax Law, to conclude that there are two types of invalidity, nullity and voidability, which relate to material and formal defects